Leading and Following (Un)ethically in Limen - Cunha, Miguel Pina e 1965-; Guimarães-Costa, Nuno; Rego, Arménio ca. 20.-21. Jh.; Clegg, Stewart 1947- (2010)
We propose a liminality-based analysis of the process of ethical leadership/followership in organizations. A liminal view presents ethical leadership as a process taking place in organizational contexts that are often characterized by high levels of ambiguity, which render the usual rules and preferences dubious or inadequate. In these relational spaces, involving leaders, followers, and their context, old frames may be questioned and new ones introduced in an emergent way, through subtle processes whose evolution and implications may not be easy to grasp even by those participating in them.
Keywords: gray areas; ethical processes; ethical followership; Ethical Leadership; Liminality